Chondropyga insignicosta, a new species of Cetoniinae (Coleoptera: Scarabaeidae) from Queensland, Australia - Hutchinson, Paul M.; Moeseneder, Christian H. (Zootaxa, 2013)
Chondropyga insignicosta, new species (Coleoptera: Scarabaeidae: Cetoniinae) is described from Queensland, Australia.